(untitled) (The Peerian Journal, 2026)
This research aims to conduct a systematic comparison between classical methods for solving transportation problems and The Shrike Optimization Algorithm (SHOA), a modern optimization algorithm. Both classical methods and SHOA were applied to a range of practical examples with varying capacities to evaluate performance in terms of solution quality, execution time, and computational effort. The results showed that classical methods yielded better results and lower-cost solutions in most cases, demonstrating their effectiveness and accuracy in achieving high-quality solutions. In contrast, while SHOA did not outperform SHOA in terms of solution quality, it was superior in execution time and computational effort, making it a suitable option for situations requiring rapid and acceptable solutions without high computational costs. These results indicate that the optimal choice depends on the nature of the application: while traditional methods offer more accurate solutions, SHOA provides a fast and practical alternative, especially for large problems requiring quick solutions.